Literatur Riview : Audit Operasional Untuk Mengukur Efektivitas Dan Efisiensi Pengelolaan Investasi Pada Dana Pensiun Inti - Rahmayanti, Putri; Al Mira, Prilly (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the implementation of operational audits and measure the effectiveness and efficiency of investment management at INTI Pension Fund. Through this research, the author conducted an operational audit using secondary data in the form of Investment Reports and INTI Pension Fund Audited Financial Statements from 2016 to 2020. This study was conducted using a literature review method by examining and analyzing 10 articles. Based on the results of the research and literature review, it can be concluded that the audit results show that the investment management at INTI Pension Fund complies with the Investment Guidelines; however, there are still some weaknesses. It can be concluded that the investment management was not effective in 2018-2020 because the return on investment (ROI) did not meet the targets set in the Investment Direction, which were 7.43%, 6.68%, and 7.68%, respectively, whereas it should have been 9%.